2008
DOI: 10.1016/j.biortech.2008.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and bioadsorption of granular activated carbon (GAC) for dissolved organic carbon (DOC) removal in wastewater

Abstract: In this study, the performances of GAC adsorption and GAC bioadsorption in terms of dissolved organic carbon (DOC) removal were investigated with synthetic biologically treated sewage effluent (BTSE), synthetic primary treated sewage effluent (PTSE), real BTSE and real PTSE. The main aims of this study are to verify and compare the efficiency of DOC removal by GAC (adsorption) and acclimatized GAC (bioadsorption). The results indicated that the performance of bioadsorption was significantly better than that of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(39 citation statements)
references
References 12 publications
2
37
0
Order By: Relevance
“…Also, the study of adsorption kinetics is highly relevant to the design of an adsorption system because it provides beneficial information in the reaction pathway, rate of adsorption and adsorption mechanism of adsorbate onto adsorbent [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the study of adsorption kinetics is highly relevant to the design of an adsorption system because it provides beneficial information in the reaction pathway, rate of adsorption and adsorption mechanism of adsorbate onto adsorbent [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have reported that GAC biofilm treatments exhibited simultaneous adsorption and biodegradation mechanisms for the removal of organic compounds from other wastewater matrices (77)(78)(79). This combination indicates the ability of GAC to bioregenerate due to the biodegradation activity of microorganisms colonizing the external surface and macropores of the GAC (80). The combined effect of adsorption and biodegradation on contaminant removal rates is dependent on the microbial abundances and compositions, their metabolic rates, and the biofilm retention time.…”
Section: Characterization Of Biofilm (I) Confocal Imagingmentioning
confidence: 97%
“…It enables microorganisms to form a biofilm or biomass that decomposes AOC (Takeuchi et al 1997) in water. The lifetime of GAC in BACF is extended by a biofilm reducing the cost of regeneration (Xing et al 2008). BACF can remove biodegradable organic matter, reduce chlorine dosage, remove bad-smelling substances or other micro-pollutants (TOC, DOC, UV 254 , and AOC), and improve the sensation of drinking water in the taste of mouth (Huang et al 2002).…”
Section: Introductionmentioning
confidence: 99%